Case studies in data driven merchandising (Data Science Salon, 2020)
"For retail businesses, inventory is simultaneously the company's greatest asset and its largest risk. Competitor pricing, markdowns, and returns all threaten the margins that drive success, and in practice, inventory doesn't always move according to plan. To win in this highly competitive and rapidly evolving industry, it's essential to have a flexible toolkit that accurately produces forecasts and intelligently adapts to unplanned inventory dynamics. In this talk, [the presenter will] outline how Nordstrom applies data science and machine learning to build a wholistic view of inventory management from assortment, through stocking with intelligent size runs, and ending with a customer experience that gets the right product to the right customer at the right time."--Resurce description page